Deskripsi Kegiatan IMTAQ (Iman dan Taqwa) dalam Upaya Pengamalan Sila Pertama “Ketuhanan Yang Maha Esa” di Sekolah Dasar - Iwan Zulkifli; Nur Pangesti Apriliyana; Nindya Adiasti (Universitas Sebelas Maret, 2025)
As time progresses, religious education, morality, and character development have weakened. However, if children possess strong religious and moral values from an early age, they are more likely to achieve optimal developmental maturity. This study aims to describe the IMTAQ (Faith and Devotion) activities as an effort to implement the First Principle of Pancasila,